Impact of the Digital Competitiveness on the Labor Market during the Fourth Industrial Revolution, 2017-2021 - Sagua Ticona, Aleli Marina Miryam (2023)
This exploratory study aimed to evaluate the impact of digital competitiveness on labor market indicators (labor productivity, informal employment, employee earnings and unemployment) during the Fourth Industrial Revolution from 2017 to 2021. Secondary data from IMD WDC and ILOSDG were analyzed using SmartPLS 4.0, employing PLS-SEM with 115 cases and 5000 bootstraps at a significance level of 0.05. The results indicate that only formative and single-item constructs were used, VIF and individual reliability were accepted. Satisfactory R2 and Q2 values were obtained for informal employment (.455, .444), employee earnings (.506, .488) and unemployment (.214, .194), but not for labor productivity. Additionally, a relationship was found between Digital Competitiveness and the indicators: informal employment (β=-.675, t=14.181, p=<.001), employee earnings (β=.712; t=16.678, p=<.001), and unemployment (β=-.462, t=6.212, p=<.001); while no relationship was observed with labor productivity (β=-.015, t=0.185, p=0.853). Therefore, it can be concluded that Digital Competitiveness did not significantly affect labor productivity but had a significant impact on reducing informal employment, increasing employee earnings and lowering unemployment rates.